2020
DOI: 10.1111/cdoe.12516
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐five‐year follow‐up of educational differences in toothache prevalence

Abstract: Objectives Nationally representative studies on socioeconomic differences in toothache prevalence are very limited, especially with a long follow‐up period. Our aim was to examine the education‐related differences in toothache prevalence among 25‐ to 64‐year‐olds in Finland during 1990‐2014. Methods We used data from the Health Behaviour and Health Among the Finnish Adult Population surveys. Data were gathered by random samples of 15‐ to 64‐year‐old Finns annually between 1990 and 2014. Response rates decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Surprisingly, our study found that older adults who brushed their teeth at least daily were more likely to have toothache and jaw or facial pain than those who did not brush their teeth. Most studies to date have suggested that less frequent toothbrushing is associated with a higher likelihood of toothache 19 . A recent study conducted in China also found that higher frequency of toothbrushing is associated with higher likelihood of having toothache among older adults.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Surprisingly, our study found that older adults who brushed their teeth at least daily were more likely to have toothache and jaw or facial pain than those who did not brush their teeth. Most studies to date have suggested that less frequent toothbrushing is associated with a higher likelihood of toothache 19 . A recent study conducted in China also found that higher frequency of toothbrushing is associated with higher likelihood of having toothache among older adults.…”
Section: Discussionmentioning
confidence: 98%
“…Older adults who smoked in the last year of life were more likely to have toothache than those who did not smoke. Previous findings have shown that smoking was related to a higher likelihood of reporting toothache 17‐19 . This may be due to an accumulated effect of dental plaque, modified saliva by tobacco, impaired wound healing and exposure of root surfaces resulting from periodontitis 33 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations